Soluções quase periódicas para equações diferenciais funcionais - Rampasso, Giane Casari [UNESP] (2015)
The purpose of this work is to nd almost periodic mild solutions for di erential equations that can be written in the form u0(t) = Au(t) + f(u(t); t); t 2 R; where A is the in nitesimal generator of a exponentially stable C0 - semigroup, X is a Banach space and f : X R ! X is an appropriate function. For this, we will study the main properties of the theory of semigroup of bounded linear operators and the theory of almost periodic functions. Moreover, we will present results that ensure the existence and uniqueness of solution for the abstract Cauchy problem, using as a tool, the semigroup theory